A CGE analysis of the impact of climate change on sustainable development: the case of High Plateaux region, Algeria - Mohammed, Touitou (Journal of Economic Development, Environment and People, 2021)
The aim of the paper is to assess the impact of climate change on sustainable development in the case of the High Plateaux region of Algeria. A baseline “climate change” scenario and an “adaptation” scenario were assessed as part of our work. The methodological approach implemented is broken down into three interconnected evaluation phases, pre-modelling phase, modelling phase and post-modelling phase. The work has shown that these complex ex-ante evaluation approaches are adaptable and applicable in the context of Algeria. Our findings indicate that climate change would have a significant impact on economic aggregates on a regional scale. It also highlighted that the calculation of a single index of the impact of environmental policies on the sustainability of arid regions confirms the hypothesis of gaining sustainability by working towards a strategy of adaptation to climate change.